Lead Adsorption in Lubricant Waste using Zeolite - 'Aini Rahmadhaniar; Ratri Ariatmi Nugrahani; Nurul Fithriyah; Titik Lestariningsih (Jurnal Rekayasa Proses, 2020)
Lubricant waste is one of the hazardous refuses which are regulated on the limit of lead content according to Government Regulations (Kep-51/MenLH/10/1995). Therefore, it is necessary to research for reducing the lead content. The purpose of this study is to understand the effect of adding adsorbents to decrease lead content in waste of lubricants taken from ships. The waste lubricant was recycled by adsorption using zeolite. Lubricant waste samples of 200 mL each were physically and chemically identified subjected to adsorption process using zeolite adsorbent whose concentrations (%w/w) were varied as follows: 7.5%, 13.25%, 14.25%, 15.75% and 17.5% with stirring speed of 150 rpm and contact time for 60 minutes. The best results were obtained at the adsorbent amount of 26.5 grams (concentration of 13.25%), for which lead content reduction reached 83%. The ANOVA F was obtained to be 13.42, and hence the study concluded that the amount of the adsorbent was related to the decrease in lead content.A B S T R A KPelumas bekas adalah salah satu limbah berbahaya yang dibatasi kadar timbalnya dalam Peraturan Pemerintah, sehingga perlu penelitian untuk menurunkan kadar timbal. Tujuan penelitian ini adalah untuk memahami pengaruh penambahan adsorben untuk menurunkan kadar timbal dalam pelumas bekas yang berasal dari mesin kapal. Pelumas bekas didaur ulang dengan adsorpsi menggunakan zeolit. Setiap sampel berisi 200 mL pelumas bekas yang telah diidentifikasi sifat fisika dan kimia-nya diadsorpsi menggunakan adsorben zeolit. Variasi konsentrasi zeolit (%w/w) yang digunakan yaitu: 7,5%; 13,25%; 14,25%; 15,75% dan 17,5% dengan kecepatan pengadukan 150 rpm dan waktu kontak 60 menit. Hasil terbaik diperoleh pada jumlah adsorben 26,5 g (konsentrasi 13,25%) dengan penurunan kadar timbal mencapai 83%. Faktor F pada hasil ANOVA adalah 13,42. Dengan demikian dapat disimpulkan bahwa terdapat korelasi antara konsentrasi adsorben dan penurunan kadar timbal.